Educational Comics Based on Creative Problem Solving With the Aid of Kvisoft Flipbook Maker Pro for Elementary School - Dahliana, Dina; Radila, Gustina; Khairunnisa, Elvira (Pusdikra-Publishing.com, 2024)
This research aims to develop and evaluate the effectiveness of using educational comics based on Creative Problem Solving (CPS) with the help of Kvisoft Flipbook Maker Pro as an interactive learning tool for elementary school students. This research adopts the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model development approach. Initial analysis was carried out to identify student needs and elementary school characteristics. Then, educational comics were developed by combining the CPS concept and Kvisoft Flipbook Maker Pro technology. Field trials were conducted to evaluate its effectiveness. The innovation of this research lies in the use of a combination of the CPS approach and interactive flipbook technology. This educational comic not only aims to convey information, but also stimulates students' creativity and problem-solving abilities through interactivity. The research results include the development of educational comics that are integrated with Kvisoft Flipbook Maker Pro. Evaluation is carried out through measuring increased student understanding, active involvement in the learning process, and positive responses from teachers and students. This research is expected to contribute to curriculum development literature by integrating creative and technological approaches in learning. In addition, it can provide new insights into the use of flipbook technology in the context of elementary education.